Control strategies of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA) Biofilms: a review / Hanis Fadhlina Hamdan, Nawal Zulkiply and Mohd Fakharul Zaman Raja Yahya - Hamdan, Hanis Fadhlina; Zulkiply, Nawal; Raja Yahya, Mohd Fakharul Zaman (Faculty of Applied Sciences, 2023)
Staphylococcus aureus is an opportunistic pathogen infecting the human respiratory tract, nasal areas, and skin. In contrast, methicillin-resistant Staphylococcus aureus (MRSA) is more pathogenic than S. aureus due to its multiple antibiotic resistance. Both S. aureus and MRSA can form biofilm and severely threaten public health worldwide. This review discusses potential strategies to prevent or control biofilm formation by S. aureus and MRSA, including disinfectants, bioactive glasses, antibiotics, drugs, medicinal plants, nanoparticles, bacteriophages, phytochemicals, and antimicrobial coating. Advanced instrumentations such as Fluorescence Microscopy (FM), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Fourier-Transform Infrared (FTIR) spectroscopy are helpful to evaluate the efficacy of different strategies used to intervene in S. aureus and MRSA biofilms.